The Role of Creative Education and Training Activities on Community Interest and Participation at West Sumatra Pavilion Taman Mini Indonesia Indah - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Fatimah, Dinda Putri; Kiswantoro, Amin (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The purpose of this study was to determine the role of educational activities and creative training on community interest and participation in the Taman Mini Indonesia Pavilion. The object of this research is the Taman Mini Indonesia Indah destination. The research location was conducted in East Jakarta City. Data collection was carried out using qualitative methods/interviews with visitors to obtain information regarding community interest and participation in the role of educational activities in TMII